Achieving Effective Social Protection for All in Latin America and the Caribbean : From Right to Reality - Ribe, Helena; Robalino, David A.; Walker, Ian (World Bank, 2012)
Slow progress in improving the coverage of Latin America and the Caribbean's (LAC's) traditional social protection (SP) programs, combined with the deepening of democracy, have led to calls for a new social contract to provide effective social protection to all citizens. This book highlights the main findings of a regional study by the World Bank, from right to reality: how Latin America and the Caribbean can achieve universal social protection by improving redistribution and adapting programs to labor markets. The report analyzes LAC's social insurance (SI) systems and highlights growing concerns about the incentives they may create and the behaviors they may incite on the part of workers, employers and service providers. It offers an economic analysis of the roots of these problems and suggests a way forward to achieve universal coverage in an equitable manner. The report argues that a coherent overall vision for the SP system should be established if such problems are to be understood and resolved. The goal is to turn the theoretical right to social protection, which is enshrined in many of the region's constitutions and laws, into a reality for all of LAC's population. A central message of the report is that SP systems need to respond to the realities of LAC's labor markets, especially the prevalence of informality and frequent changes of employment.